An artificial photosynthetic system with CO2-reducing solar-to-fuel efficiency exceeding 20%. Issue 35 (28th August 2020) - Xiao, Yanjun; Qian, Yao; Chen, Anqi; Qin, Tian; Zhang, Fan; Tang, Hehua; Qiu, Zetian; Lin, Bo-Lin
Abstract : Artificial photosynthetic systems store solar energy in chemical fuels via CO2 reduction or renewable hydrogen evolution from water splitting. Abstract : Artificial photosynthetic systems store solar energy in chemical fuels via CO2 reduction or renewable hydrogen evolution from water splitting. But only relatively moderate CO2 -reducing solar-to-fuel efficiency ( η STF < ca. 18%) was achieved previously even using the most active gold-based electrocatalyst for the CO2 reduction reaction (CO2 RR), which is much lower than the current highest solar-to-hydrogen efficiency ( η STH = 30%). Here, we report a strategy based on a monolithic nanoporous silver-based membrane electrocatalyst ( npm -Ag) to increase the density of active sites while breaking the three-phase diffusion-limit length of previous membrane electrodes, improving the effective thickness of the catalyst layer from tens of nanometers to several micrometers without any polymer additive. The npm -Ag showed exceptionally selective reduction of CO2 to CO at low overpotentials ( ca. 80%@40 millivolts, ca. 100%@90–290 millivolts). The catalyst also allowed a nearly full use of the photocurrent of the state-of-the-art solar cells and gave a projected maximum η STF of ca. 25%. Combined with a NiFe-based O2 -evolving anode, a stable CO2 -reducing photosynthetic system with an η STF of ca. 20.1% was demonstrated experimentally for 28 hours in the absence of a DC/DC converter.